Molecular Characterization and Differential Expression of Virulence Genes in Pseudomonas aeruginosa Isolates from Diverse Clinical Sources - Hassan, Riyam Wissam (American Journal of Biomedicine and Pharmacy, 2026)
Background: Different types of illnesses, like burns, wounds and urinary tract infections, caused by pathogen Pseudomonas aeruginosa. This is because having a wide range of virulence factors, which allow it to harm the host’s immune defenses and cause damage. Objectives: The aim of this study was to isolate P. aeruginosa from different clinical sources and investigate molecular detection of virulence genes and the variation in gene expression of exoT, exoU, in P. aeruginosa isolates. Materials and Methods: Collected eighty samples from various clinical sources such as burns, wounds and urine infection from patients attending to AL-Diwaniyah Teaching Hospital and Burns Hospital in AL-Diwaniyah governorate, from period 1/10/2024 to 1/1/2025. The samples were cultivated on culture media and depending on microscopic, morphological traits, biochemical tests and Vitek system the isolates were identified. Technique polymerase chain reaction (PCR) was used to molecular detect of (exoT, exoU) genes and technique Real Time PCR examined the gene expression of (exoT, exoU) genes in P. aeruginosa isolates. Results: The results revealed that P. aeruginosa isolates constituted 12 (15%) of the total samples, distributed among five isolates from burns and five from wounds, representing 16% and 14%, respectively, and two (13%) isolates from urine samples. The results showed that all isolates contained exoT and exoU genes at a rate 100%. Significant differences were observed in the level of gene expression of the genes, as it was found in P. aeruginosa isolates from wounds, exoU gene showed the highest level of gene expression (22.53±14.21a) compared to the rest of the clinical sources. In contrast, exoT gene expression level was found to be relatively stable across all isolates. Conclusion: P. aeruginosa is a pathogen that causes urinary tract infections, burns, and wounds. Virulence genes exoT, exoU were present in all isolates, but the most highly expressed gene in wound samples was exoU compared to the rest of the clinical sources.